Pengaruh Literasi Keuangan, Kemudahan Dan Kemanfaatan Terhadap Minat Penggunaan E-Money pada Mahasiswa Akuntansi di Kota Batam - Karin Legiana Wijayanti; Hermaya Ompusunggu (eCo-Buss, 2024)
This research aimed to assess the influence of financial literacy, convenience, and expediency on the adoption of e-money among accounting students in Batam City during the academic year 2022. The study population comprised a total of 1,234 students, and data were collected from a sample of 302 students through online questionnaires distributed via Google Forms. The findings of the study indicate significant relationships between the variables examined: Firstly, financial literacy was found to have a notable impact on the interest in using e-money. The regression coefficient value of 0.244, along with a calculated t-value greater than the critical t-table value (5.610 > 1.96795), demonstrates the significance of this relationship. Secondly, convenience plays a crucial role in influencing the interest in using e-money. The regression coefficient of 0.347, coupled with a calculated t-value exceeding the critical t-table value (14.212 > 1.96795), emphasizes the significance of this aspect. Lastly, expediency also has a meaningful impact on the interest in using e-money, with a regression coefficient of 0.110 and a calculated t-value surpassing the critical t-table value (4.981 > 1.96795). These findings suggest that improving financial literacy, enhancing convenience, and promoting expediency in e-money usage could positively influence accounting students' interest in adopting e-money as a payment method. Further recommendations may include the development of educational programs to boost financial literacy and ensuring the user-friendliness of e-money platforms to enhance convenience and expediency for potential users.)